PENELITIAN EVALUASI PENDIDIKAN - Muhammad Toriqularif (ADDABANA: Jurnal Pendidikan Agama Islam, 2019)
To know the intricacies of something needed in a study, it was done to get an answer from the occurrence of something using scientific methods. In the world of research, there are at least two types of research, namely qualitative and quantitative. The following will be discussed about the evaluation research, in the world important research evaluation education is conducted in order to measure progress and further develop in a better direction. In principle, evaluation studies to make decisions by comparing data or information collected against criteria, standards, or benchmarks used as comparators for the data obtained. While evaluation is a systematic and ongoing process to determine the quality (value and meaning) of something, based on certain considerations and criteria in the framework of decision making. Among the evaluation models referred to IS; CIPP evaluation Model, UCLA Model evaluation, Brinkerhoff Model and Stake Model or Countenance Model. Meanwhile, evaluation research can be divided into two types, namely formative evaluation, and summative evaluation. The standard procedures in evaluation research are as follows; Clarification of reason to evaluate (explain the reasons why evaluation is held), choose Evaluation model, identify related parties, determination of components to be evaluated, identify evaluation questions, Compiling design evaluation and schedule of activities, collection, and analysis of data, reporting of evaluation results. Keywords: research, evaluation, and education